The recent trend of twin epidemic in the United States: a 10-year longitudinal cohort study of co-prescriptions of opioids and stimulantsResearch in context - Seungyeon Lee; Wenyu Song; David W. Bates; Richard D. Urman; Ping Zhang (The Lancet Regional Health. Americas)
Summary: Background: In recent years, the use of central nervous system stimulant medications has increased among the population already using opioids, referred to as a “twin epidemic.” There is an increasing concern about its harmful outcomes in large populations. However, very few studies examined the co-prescription pattern of these two drug categories over a long period, and there is currently no clear restriction on stimulant prescriptions among patients under opioid treatment in the United States. The objectives of our study were to identify opioid prescription dosage time-dependent patterns and patient subgroups representing distinct trajectories on a national level in the recent 10 years, and to further investigate longitudinal associations between stimulant and opioid prescriptions and the impact of stimulant prescriptions on opioid dosage patterns. Methods: We obtained patient records from MarketScan, one of the largest clinical databases of health insurance in the United States. 10 years (2012–2021) of prescription records and related patient profiles, who received at least two independent opioid prescriptions, were utilized for developing a group-based opioid dose trajectory model. Findings: From an initial cohort including 22 million patients with 96 million opioid prescriptions, we developed a study cohort of 2,895,960 patients with a mean age of 43.9 years (standard deviation [SD] 13.0), of whom 1,244,077 (43%) were male. Significant geographical variations in opioid prescription frequency and dosage among four U.S. regions were observed. The trajectory model identified five distinct opioid dose groups. Stimulant prescription before the initial opioid prescription was positively associated with escalating opioid doses (odds ratio [OR]: 7.58; 95% confidence intervals [CI] 6.14–9.35, opioid dose increasing group compared to the decreasing group). Stimulant co-prescriptions were also associated with increasing opioid doses (OR: 1.73; 95% CI 1.40–2.14) and were identified in patients with a higher prevalence of opioid use disorder. Interpretation: During the recent 10 years, stimulant prescription is positively associated with escalating opioid prescription activities in U.S. healthcare systems, suggesting co-prescriptions of these two types of drugs are an important contributing factor for a national-level twin epidemic. Healthcare leaders and policymakers should pay more attention to this issue and its potential harms. Funding: National Institute of General Medical Sciences, National Institute on Drug Abuse, and National Science Foundation.